Systemic Treatment Of Murine Mammary Adenocarcinoma Transplanted Subcutaneously In Mice By Virulance Newcastle Disease Viruse - AbdulAmeer O. Ismail; T. A. Makkawi; Nahi Y. Yaseen; Anton S. Albana (Kufa Journal for Veterinary Medical Sciences, 2010)
The present  study  included  of  six  groups of  femals mouse  injecting  with cells from murine mammary adenocarcinoma subcutaneously, three  groups  as  treated and the others as control groups. The  first  group, Which  was  treated  with  BCG  and injection of virulence Newcastle disease virus(NDV) intraperitonealy (I.P),showed prominent   suppression  of  tumor  statistically significant  with ( 53 % ) compared  with  group  of  negative  control  and (46%) compared  with group of positive control . The groups treated with (NDV),shown increase of relative  tumor volume(RTV) compared with tumor size at the start of treatment but these increased lower than increased will be occurs in untreated groups.   Grossly,The treated tumor characterized by small in size,firm compared with tumor size in untreated groups.Histopathological examination   of   the  treated   tumor  showed  wide  areas  of  necrosis associated with  lymphocytic ,plasmic   and   macrophagic infiltration.